Identification of a mitochondrial‐targeting secretory protein from Nocardia seriolae which induces apoptosis in fathead minnow cells. Issue 11 (3rd September 2019) - Chen, Jianlin; Xia, Liqun; Wang, Wenji; Wang, Zhiwen; Hou, Suying; Xie, Caixia; Cai, Jia; Lu, Yishan
Abstract: Nocardia seriolae is the main pathogen responsible for fish nocardiosis. A mitochondrial‐targeting secretory protein (MTSP) 3141 with an N‐terminal transit peptide (TP) from N. seriolae was predicted by bioinformatic analysis based on the genomic sequence of the N. seriolae strain ZJ0503. However, the function of the MTSP3141 and its homologs remains totally unknown. In this study, mass spectrometry analysis of the extracellular products from N. seriolae proved that MTSP3141 was a secretory protein, subcellular localization research showed the MTSP3141‐GFP fusion protein co‐localized with mitochondria in fathead minnow (FHM) cells, the TP played an important role in mitochondria targeting, and only the TP located at N‐terminus but not C‐terminus can lead to mitochondria directing. Moreover, quantitative assays of mitochondrial membrane potential (ΔΨm) value, caspase‐3 activity and apoptosis‐related gene ( Bcl ‐ 2, Bax, Bad, Bid and p53 ) mRNA expression suggested that cell apoptosis was induced in FHM cells by the overexpression of both MTSP3141 and MTSP3141ΔTP (with the N‐terminal TP deleted) proteins. Taken together, the results of this study indicated that the MTSP3141 of N. seriolae was a secretory protein, might target mitochondria, induce apoptosis in host cells and function as a virulence factor.